Kontribusi Kepemimpinan Autentik, Supervisi Akademik, Etos Kerja dan Motivasi Kerja Terhadap Kinerja Guru SMP Negeri 6 Singaraja - K.I. Permatasari; I.M. Yudana; I.N. Natajaya (Jurnal Administrasi Pendidikan Indonesia, 2021)
The purpose of this study was to reveal the contribution of authentic leadership, academic supervision, work ethic and work motivation to the teacher's performance at SMP Negeri 6 Singaraja. This research is an ex post facto research. A sample of 30 teachers was taken by random sampling technique from the research population, which amounted to 60 teachers at SMP Negeri 6 Singaraja. The independent variables were authentic leadership (X1), academic supervision (X2), work ethic (X3) and work motivation (X4), while the dependent variable was teacher performance (Y). The research data was collected by using a questionnaire method. Data were analyzed using multiple linear regression and partial correlation. The test results with the SPSS program showed that: 1) Authentic Leadership contributes positively and significantly to Teacher Performance by 41.5%, with an effective contribution of 0.1868%, 2) Academic Supervision contributes positively and significantly to Teacher Performance by 55.5% with an effective contribution of 11.2%. , 3) Work ethic contributes positively and significantly to Teacher Performance by 88.8% with an effective contribution of 31.48%, 4) Work Motivation contributes positively and significantly to Teacher Performance by 91% with an effective contribution of 51.46%, 5) Authentic Leadership, Academic Supervision , Work ethic and work motivation have a positive and significant contribution simultaneously to teacher performance at SMP Negeri 6 Singaraja by 93.4%.